A robust cursor activity control with Iris gesture and blink detection technique - Islam, Md. Rayhan Al; Rahman, Maliha; Rezyuan, Md. (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.